Selenophysics and models of the lunar three-layered mantle - E.V. Kronrod; Y.A. Nefedyev; V.A. Kronrod; O.L. Kuskov; A.O. Andreev (Учёные записки Казанского университета: Серия Физико-математические науки)
The paper focuses on analyzing the data produced by the modern space missions. The purpose of the work is to analyze the lunar gravitational field and dynamic figure, problem of the lunar core existence and to determine petrologic and geophysical parameters of the composition and structure of the lunar mantle using computer simulation. The analysis of space observations has shown that the real physical figure of the Moon is a more complex system than the model that can be described by a triaxial ellipsoid; at the same time, absolute values and orientation of the inertia moments can be determined neither from space observations nor from ground-based ones. Only the combinations of the inertia moments can be determined. On the basis of the study of trajectories of seismic waves passing and features of their reflection from the lunar inner layers produced by the Apollo mission's seismographs, the composition and structure of the lunar core layers at various depths have been determined. The results of the lunar core studies confirm the hypothesis that the Moon was formed 4.5 billion years ago as a result of the Earth's collision with a large space object. Petrologic and geophysical investigation includes the solution of two problems. The first one is the construction of a three-layered lunar mantle chemical composition model on the basis of a joint inversion of gravitational, seismic, and petrologic and geochemical data. The second problem consists in the revelation of a degree of the mantle reservoirs' chemical homogeneity, namely whether the mantle is homogeneous or stratified by chemical composition with different concentrations of petrogenic elements in various zones of the mantle. Based on the inversion of gravitational and seismic data, inherently coherent models of chemical composition, mineralogy, and lunar three-layered mantle rates have been developed. The results of the simulation have shown that the models of the lunar mantle's thermal state are enriched by SiO2, FeO and depleted by MgO in relation to the primitive Earth's mantle, which indicates the significant distinction between the compositions of the Earth and Moon.